Wind and tornado climatologies and wind resource modelling for a modern development situated in "Tornado Alley". (January 2018) - Romanic, Djordje; Parvu, Dan; Refan, Maryam; Hangan, Horia
Abstract: The Kansas Project aims to establish a synergetic link between people and weather, as well as to explore different ways to harness the weather for its sustainable resources. The site is located in the South Central Kansas, United States. This case study presents wind and tornado climatology analyses coupled with a wind resource assessment study for this modern development. The wind analyses are conducted using wind data from weather station located in Medicine Lodge and for the period 1984–2015. The mean annual wind speed at the site is 4.45 m s −1 at 10 m height. The north-south bi-directionality of the wind rose is very pronounced. The mean annual wind speeds have a positive, but statistically not significant trend. A 50-year return period 5-s gust of 34 m s −1 is estimated at 10 m height. The deadliest and most damaging tornadoes around the site are F3 twisters, while the most common tornadoes are F2 and weaker. The WAsP package is used to calculate the regional wind atlas for five heights and five reference roughness lengths. Wind resource grids depict good wind energy potential at 50, 80, 100 and 150 m levels. In addition, roughness and topographic uncertainties related to WAsP performance are addressed in details. Graphical abstract: Highlights: The Kansas Project is a modern, sustainable development in South Central Kansas. Comprehensive wind and tornado climatology of the site presented and discussed. Wind resource assessment study conducted using WAsP. Wind potential evaluated at four heights and wind turbine locations determined. Uncertainties in the estimated wind resources analyzed quantitatively.